2016
DOI: 10.3847/0004-637x/829/2/68
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the Radius of the Convective Core of Main-Sequence Stars From Observed Oscillation Frequencies

Abstract: The determination of the size of the convective core of main-sequence stars is usually dependent on the construction of models of stars. Here we introduce a method to estimate the radius of the convective core of main-sequence stars with masses between about 1.1 and 1.5 M ⊙ from observed frequencies of low-degree p-modes. A formula is proposed to achieve the estimation. The values of the radius of the convective core of four known stars are successfully estimated by the formula. The radius of the convective co… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 47 publications
2
5
0
Order By: Relevance
“…While this is exactly the same range of values as in the 2.0 M star, we should note that for the 1.5 M star f ov = 0.005 gives a mixing rate that is only one order of magnitude larger than in the f ov = 0.01 run, indicating that the ideal value of f ov is much closer to 0.005 than to 0.01 considering that the same comparison in the 2.0 M star results in a difference of three orders of magnitude in ṀX . Asteroseismic observations by Yang (2016), on the other hand, suggest that the core of the ≈ 1.4 M Kepler star KIC 9812850 has a radius of 0.140 ± 0.028 R , which is in good agreement with the initial model of H1.5-ov1.0. This 1.5 M models also allowed us to estimate a diffusion coefficient without the need of tracer particles.…”
Section: 5msupporting
confidence: 65%
“…While this is exactly the same range of values as in the 2.0 M star, we should note that for the 1.5 M star f ov = 0.005 gives a mixing rate that is only one order of magnitude larger than in the f ov = 0.01 run, indicating that the ideal value of f ov is much closer to 0.005 than to 0.01 considering that the same comparison in the 2.0 M star results in a difference of three orders of magnitude in ṀX . Asteroseismic observations by Yang (2016), on the other hand, suggest that the core of the ≈ 1.4 M Kepler star KIC 9812850 has a radius of 0.140 ± 0.028 R , which is in good agreement with the initial model of H1.5-ov1.0. This 1.5 M models also allowed us to estimate a diffusion coefficient without the need of tracer particles.…”
Section: 5msupporting
confidence: 65%
“…The distance of the overshooting of a convection is defined as δ ov H p , where δ ov is a free parameter and H p is the local pressure scale-height. Recently, Yang (2016b) developed a method to determine the size of the convective core including the overshooting region from observed oscillation frequencies of low-degree p-modes. It was found that the value of δ ov is variable for stars with an approximatelly equal mass.…”
Section: Introductionmentioning
confidence: 99%
“…It thus can counteract the effect of enhanced diffusion on the surface helium abundance (Yang 2019), i.e., it can improve the prediction of the surface helium abundance. The effects of rotation on the low-Z models were studied by Yang & Bi (2007), Turck-Chièze et al (2010, and Yang (2016Yang ( , 2019. However, the rotating models with AGSS09 mixtures (Yang 2019) disagree with the detected neutrino fluxes of Borexino Collaboration et al (2018Collaboration et al ( , 2020.…”
Section: Introductionmentioning
confidence: 98%
“…The standard solar models (SSMs) constructed in accordance with the high metal abundances (old solar abundances, e.g., GS98) are considered to be in good agreement with the seismically inferred sound-speed and density profiles, depth, and helium abundance of the CZ, but the SSMs constructed in accordance with the low metal abundances (revised solar abundances) do not completely agree with the seismically inferred results Basu & Antia 2004;Yang & Bi 2007;Basu et al 2009;Serenelli et al 2009Serenelli et al , 2011Zhang & Li 2012) and the neutrino flux constraints Turck-Chièze et al 2010Yang 2016), which is known as the solar modeling problem or solar abundance problem (Basu et al 2015;Amarsi et al 2021;Christensen-Dalsgaard 2021;Salmon et al 2021).…”
Section: Introductionmentioning
confidence: 99%